Prevalence of the attributes of the Female Athlete Triad in competitive Nigerian female athletes - Akinyemi, J. S.; Otinwa, G. O. (American Journal of Sports Science, 2025)
The Female Athlete Triad syndrome describes three interrelated conditions: low energy availability with or without disordered eating, menstrual dysfunction, and poor bone health, inclusive of low bone density and bone stress injury. Sports participation for female athletes has risen exponentially; however, investigations into the health and wellbeing of female athletes from Africa are extremely limited because these groups are noticeably absent from the Triad literature. This research gap can have negative health implications, on the Female Athletes in Nigerian athletes. Purpose: To investigate the prevalence of Triad components in competitive Nigerian female university athletes as well as explore hematological markers. Methods: n=71, (21.8±0.3yrs) and BMI (22.5±0.6 kg/m2) female athletes from the University of Lagos, during the Nigeria University Games Competition, completed a Health, Exercise Nutritional Survey questionnaire to provide demographics, medical history, exercise, and dietary practices. Athletes consented to a complete blood count (CBC) assessment: white blood cell (WBC), hematocrit (HCT), red blood cell (RBC), hemoglobin (HGB) and platelets. Results: Exercise frequency was 4.6±0.3 days/wk., overtraining, 6.8%, age at menarche 12.8±0.1 yrs., and gynecological age 9.2 ±0.5 yrs. Factors reflecting energetic status include (20/71): 28% reported eating a low-fat diet, (27/71) 38% dieted to lose weight to change their body composition and to improve performance, (2/71) 3% reported a history of anorexia and Bulimia. Prevalence of oligomenorrhea was (11/71) 15% while amenorrhea was (14/71) 19%. Stress fracture was reported to be (9/71) 13% and (3/71) 4%, had a family history of osteoporosis. (24/71) 34% refrained from training due to injuries during the past year and (7/71) 9.8% reported illness due to exercise. CBC measures showed RBC (3.95±0.06 1012/L), HGB (10.64±0.11 g/dL), HCT (32.68±0.31%) WBC (5.20±0.14 109/L) and platelets (245.17±8.2 *109/L), demonstrating that RBC and WBC are within the normal range while HGB, HCT and platelets are abnormal. Athletes in endurance sports had a decreased hematocrit (HCT). Conclusion: A significant percentage of Nigerian female athletes participating in the NUGA Games demonstrated factors reflective of poor energy intake, menstrual dysfunction and bone health including a history of stress fractures and absence from sport due to injury. The prevalence of factors observed suggests the need to advance screening tools and education efforts to include randomized clinical trials, optimize health of athletes and provide information for future investigation into the Triad among Nigerian athletes.